A cross-sectional study for determining the perception and preferences of immunity boosters for protection against COVID-19 - Nanavaty, Dhairya P.; Sanghvi, Ankushi A.; Mehta, Manav S.; Gupta, Sarbari; Dumra, Gurusharan (International Journal of Advances in Medicine, 2020)
Background: The World Health Organisation declared the novel coronavirus (COVID-19) outbreak as a global pandemic on March 11, 2020. The consumption of vitamins, especially C, D, and zinc, hydroxychloroquine, and Arsenicum album 30 (homeopathy), has increased tremendously. However, the clinical trial showing the benefits of these agents is still underway though there have been a lot of discussion about these in print, electronic, and social media. Method: A questionnaire-based observational study was conducted. The participants were inquired about the use of any type of immunity booster by them and the source of information regarding the same. The data was analysed using Excel and Python. Results: Our study included 1147 participants. A dramatic increase of 21.97% in the consumption of immunity-boosting agents after the COVID-19 outbreak was observed, maximally in Ayurveda. The major source of information for immunity-boosters was provided by friends/family/relatives (50.4%). 52.7% of the respondents selected Ayurveda as their preferred choice of immunity booster (prophylaxis). If the respondents were to develop any of the COVID-19 symptoms, the majority (45.1%) decided to contact their family doctor, and 53.7% chose Allopathy as their preferred system for treatment. 91.5% of the respondents agreed to take a vaccine if it develops. Conclusion: There has been a boom in the immunity booster drug market because people are selecting immunity boosters despite no scientific background. It is imperative to educate people regarding the same and also conduct research studies to find benefits, if any.